Ni nanocrystals on HOPG(0001): A scanning tunnelling microscope study - Marz, Michael; Sagisaka, Keisuke; Fujita, Daisuke (Beilstein Journal of Nanotechnology, 2013)
The growth mode of small Ni clusters evaporated in UHV on HOPG has been investigated by scanning tunnelling microscopy. The size, the size distribution, and the shape of the clusters have been evaluated for different evaporation conditions and annealing temperatures. The total coverage of the surface strongly depends on the evaporation rate and time, whereas the influence of these parameters is low on the cluster size. Subsequent stepwise annealing has been performed. This results in a reduction of the total amount of the Ni clusters accompanied by a decreasing in the overall coverage of the surface. The diameter of the clusters appears to be less influenced by the annealing than is their height. Besides this, the cluster shape is strongly influenced, changing to a quasi-hexagonal geometry after the first annealing step, indicating single-crystal formation. Finally, a reproducible methodology for picking up individual clusters is reported .
Keywords: clusters; growth mode; Ni; nickel